Midnight sun - Meyer, Stephenie, 1973- (New York : Little, Brown and Company, 2020)
This tale as told through Edward's eyes takes on a new and decidedly dark twist.
"Megan Tingley books."
Keywords: Cullen, Edward -- (Fictitious character) -- Juvenile fiction; Swan, Bella -- (Fictitious character) -- Juvenile fiction; Vampires -- Juvenile fiction; Interpersonal relations in adolescence -- Juvenile fiction; High school students -- Juvenile fiction; High schools -- Juvenile fiction; Young adult fiction; Fantasy fiction; Paranormal fiction; Romance fiction